PERLINDUNGAN HAK ASASI MANUSIA PENGUNGSI INTERNASIONAL - Torry Satriyo Kusumo, Ayub (Faculty of Law, Universitas Sebelas Maret, 2012)
AbstractRefugees are a group of people who were forced to leave the country because of very threatening fear. Fear is often due to natural disasters or conflict. In countries receiving refugees, they often experience inhumane treatment such as rape, assault, discrimination, repatriated by force, those lead to the violation of human rights. There has been regulation for human rights in refugee issues both internationally and regionally, for instance Convention related to Status of Refugee 1951 and The Protocol related to the Status of Refugee 1967. There are at least five basic rights of refugees, they are the right to be protected from returning to the country of origin forcibly (non refoulement), the right to seek asylum, the right to obtain equality and non-discrimination, the right to live and to be secured, as well as the right to return home. AbstrakPengungsi adalah kelompok orang yang dipaksa untuk meninggalkan suatu negara karena takut yang sangat mengancam, dapat disebabkan oleh bencana alam atau konflik. Di negara-negara penerima, pengungsi sering mengalami perlakuan tidak manusiawi seperti perkosaan, penganiayaan, diskriminasi, dipulangkan secara paksa yang mengarah pada pelanggaran hak asasi manusia. Ada pihak-pihak yang telah menetapkan hak asasi manusia dalam masalah pengungsi baik internasional maupun regional, seperti Konvensi Status Pengungsi dari tahun 1951 dan Protokol yang berkaitan dengan Status Pengungsi 1967. Setidaknya ada lima hak dasar pengungsi, yaitu hak atas perlindungan dari kembali ke negara asal secara paksa (refoulement non), hak untuk mencari suaka, hak untuk mendapatkan kesetaraan dan non-diskriminasi, hak untuk hidup dan keamanan, serta hak untuk pulang.